A V-Shape Optical Pin Interface for Board Level Optical Interconnect - Saris, Nur Najahatul Huda; Mikami, Osamu; Hamzah, Azura; Ambran, Sumiaty; Fujikawa, Chiemi (Photonics Letters of Poland, 2018)
This paper introduces a new interface of an optical pin for Printed Circuit Boards (PCBs), the V-shape cut type which is an innovation from the 90-degree cut type optical pin. The effectiveness is determined by optical characteristics through OptiCAD and by experiment. The simulation used a model of ray tracing analysis which is a one to two (split) connection function model. For the experiment, a Polymer Optical Fibre (POF) V-shape optical pin has been fabricated. It was found that the V-shaped optical pin has a multi-branched function and is applicable to optical interconnection. Full Text: PDF References Mikami, O., et al. Optical pin interface for 90-deg optical path conversion coupling to Printed Wiring Board. in Region 10 Conference (TENCON), 2016 IEEE. 2016. IEEE. CrossRef DeCusatis, C., Data center architectures, in Optical Interconnects for Data Centers. 2017, Elsevier. p. 3-41. CrossRef Duranton, M., D. Dutoit, and S. Menezo, Key requirements for optical interconnects within data centers, in Optical Interconnects for Data Centers. 2017, Elsevier. p. 75-94. CrossRef ITOH, Y., et al., Optical Coupling Characteristics of Optical Pin with 45° Micro Mirror for Optical Surface Mount Technology. Journal of The Japan Institute of Electronics Packaging, 2001. 4(6): p. 497-503. CrossRef Uchida, T. and O. Mikami, Optical surface mount technology. IEICE Transactions on Electronics, 1997. 80(1): p. 81-87. CrossRef Papakonstantinou, I., et al., Low-cost, precision, self-alignment technique for coupling laser and photodiode arrays to polymer waveguide arrays on multilayer PCBs. IEEE Transactions on Advanced Packaging, 2008. 31(3): p. 502-511. CrossRef Nakama, K., et al., Optical connection device. 2006, Google Patents. DirectLink Ramaswami, R., K. Sivarajan, and G. Sasaki, Optical networks: a practical perspective. 2009: Morgan Kaufmann. DirectLink Tong, X.C., Advanced materials for integrated optical waveguides. 2014: Springer. CrossRef